CO2 Fixation and Catalytic Reduction by a Neutral Aluminum Double Bond. (28th June 2019) - Weetman, Catherine; Bag, Prasenjit; Szilvási, Tibor; Jandl, Christian; Inoue, Shigeyoshi
Abstract: CO2 fixation and reduction to value‐added products is of utmost importance in the battle against rising CO2 levels in the Earth's atmosphere. An organoaluminum complex containing a formal aluminum double bond (dialumene), and thus an alkene equivalent, was used for the fixation and reduction of CO2 . The CO2 fixation complex undergoes further reactivity in either the absence or presence of additional CO2, resulting in the first dialuminum carbonyl and carbonate complexes, respectively. Dialumene (1 ) can also be used in the catalytic reduction of CO2, providing selective formation of a formic acid equivalent via the dialuminum carbonate complex rather than a conventional aluminum–hydride‐based cycle. Not only are the CO2 reduction products of interest for C1 added value products, but the organoaluminum complexes isolated represent a significant step forward in the isolation of reactive intermediates proposed in many industrially relevant catalytic processes. Abstract : Die Anlagerung von CO2 an eine Aluminium‐Aluminium‐Doppelbindung vermittelt die katalytische und stöchiometrische CO2 ‐Reduktion unter milden Bedingungen.